Quantitatif Structure-Activity Relationship Analysis of a Carbazole Analog Compounds as Antibacterial using Electronical Descriptors - Islamudin Ahmad (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2014)
The Quantitatif Structure-Activity Relationship (QSAR) study has been established on 13 Carbazole analog compounds to their antibacterial activity using electronical descriptors. The development of computational chemistry, in particular quantum chemical calculation progression, has made the possibility of molecule modeling and pharmacochemistry exploration of molecule structures. This emerging semiempirical method can be implemented in QSAR using Hansch model. A research associated with QSAR antibacterial activity of Carbazole analog compounds which used semiempirical AM1 (Austin Model 1) method has been conducted. The geometrical optimation of 2D into 3D structures was done utilizing HyperChem program with the Polak – Ribiere algorithm. Results revealed that atom in the position C8, C9, C10 and C12 are necessary to predict biological activity of Carbazoleanalog. Keywords: QSAR, Atomic Net Charges, Cross Validation Methods